Smart safety harness / Muhammad Zarith Idham Zalin and Mohamad Hamdan Othman - Zalin, Muhammad Zarith Idham; Othman, Mohamad Hamdan (2023)
The construction industry in Malaysia has become one of the sectors with the highest growth rate. As a result of this growth, the demand for safety harnesses has also increased as many high-rise buildings are constructed nowadays. Personal Protective Equipment (PPE) is an important equipment that is worn by construction workers to protect themselves from risks of workspace hazards that can lead to serious injuries. In this study, safety harness was selected as one of the PPE options for innovation. It is anticipated to improve the performance of this equipment, ultimately making construction tasks both easier and safer. Based on the previous research, there are various challenges relating to the use of safety harness that might compromise the comfort and safety of the construction workers. By identifying these significant challenges, novel solutions can be proposed. In view of that, this study aims to improve the existing safety harness by applying new technological innovations that can provide enough safety to the construction workers.